2006
DOI: 10.1021/jo0526284
|View full text |Cite
|
Sign up to set email alerts
|

Regioselective Reductive Openings of Acetals; Mechanistic Details and Synthesis of Fluorescently Labeled Compounds

Abstract: Regioselective reductive openings of mixed phenolic-benzylic acetals, using BH3.NMe3-AlCl3, was investigated, and a mechanism where the outcome is directed by the electrostatic potential of the two oxygen atoms is presented. The regioselective acetal opening was used in the synthesis of a fluorescently labeled analogue to antiproliferative xylosides. The fluorescently labeled xyloside was tested for uptake, antiproliferative activity, and glycosaminoglycan priming in different cell lines. The xyloside was take… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
16
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 39 publications
1
16
0
Order By: Relevance
“…This is in accordance with Johnsson et al who found out that the dansyl group attached xylosides were unable to prime any detectable amount of GAG chains. 18 Fluorophore-tagged xylosides without a charged group are next chosen to be synthesized. Fluorophore-tagged xylosides ( 4 , 9 , 13a , and 13b ), in which xylose residue is attached to 1-pyrene butyrate and UMB derivatives, were synthesized.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in accordance with Johnsson et al who found out that the dansyl group attached xylosides were unable to prime any detectable amount of GAG chains. 18 Fluorophore-tagged xylosides without a charged group are next chosen to be synthesized. Fluorophore-tagged xylosides ( 4 , 9 , 13a , and 13b ), in which xylose residue is attached to 1-pyrene butyrate and UMB derivatives, were synthesized.…”
Section: Resultsmentioning
confidence: 99%
“…1517 Earlier studies examined several other fluorophore-tagged xylosides for studying the mechanism of GAG biosynthesis and GAG priming activity. 18 These studies have shown successful internalization of fluorophore-conjugated xylosides into the para- and perinuclear regions of the cells. However, these molecules were unfortunately not found to initiate GAG biosynthesis suggesting that either these fluorophore xylosides failed to reach GAGOSOMES where GAG biosynthetic enzymes reside within the complex Golgi apparatus or biosynthetic enzymes could not recognize these fluorophore-conjugated xylosides after these molecules reach GAGOSOMES.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, the regioselectivity in THF is dependent on the type of borane (i.e., BH 3 complexed to NMe 3 or THF) used for the reduction rather than the Lewis acid (e.g., AlCl 3 , BF 3 ÁOEt 2 , In(OTf) 3 , AgOTf, or Cu(OTf) 2 ) (Scheme 13). 26,31,50,52,53 In addition, openings of less sterically hindered substrates indicate that the origin for the selectivity must be stereoelectronical rather than steric. Thus, openings of substrate 56 (Scheme 14) gave interesting results.…”
Section: Mechanismmentioning
confidence: 99%
“…8 The reagent BH 3 .NMe 3 -AlCl 3 has been used to bring about reductive opening of acetals. 9 With mixed phenolic-benzylic acetal as reactant, the reagent acts regioselec-tively (in THF at 0 • C), yielding a benzylic ether and free phenol, probably because the borane first associates with the more basic benzylic oxygen. Conditions to bring about the inverse opening are being sought.…”
mentioning
confidence: 99%